Epidemiology of Pertussis After the COVID-19 Pandemic: Analysis of the Factors Involved in the Resurgence of the Disease in High-, Middle-, and Low-Income Countries - Lucia F. Bricks; Juan C. Vargas-Zambrano; Denis Macina (Vaccines)
Pertussis is a highly contagious bacterial disease of the respiratory tract that can be prevented by vaccination. Before the COVID-19 pandemic, the vaccine coverage rate for the third dose of a DPT-containing vaccine was 86%, with large disparities among countries. Since 2022, many high-income countries have reported a resurgence of pertussis, especially in the European region, but the disease has also caused outbreaks in middle- and low-income countries, despite their less extensive disease surveillance capacities. This paper aims to review the incidence rates (IRs) of pertussis in high-, middle-, and low-income countries following the COVID-19 pandemic and to discuss the most relevant factors associated with the resurgence of the disease. The epidemiology of pertussis is highly variable and is influenced not only by the type of vaccine used but also by the specific characteristics of the disease, vaccine coverage rates, vaccination schedules, and the quality of surveillance. Since the cessation of COVID-19 measures, there have been significant pertussis outbreaks that could have been partially mitigated with higher coverage rates and more comprehensive pertussis vaccination throughout life.